Analisis Peran Psikologi Agama Dalam Pembentukan Karakter dan Jiwa Agama Pada Remaja - Ahya Bismika; Ilham Iman Nur Dharmawan (ARIMA : Jurnal Sosial Dan Humaniora, 2023)
Abstract The development of adolescents is greatly influenced by the environment around them. Especially the role of religion in the formation of adolescent character and personality. The role of religious psychology in adolescent development is very complex because it relates to nature and belief in religious teachings, truth values and also makes religion a guide in attitudes and behavior. The development of a person's religious views is in line with his physical and spiritual development. Because adolescence is a period where a person is still looking for his identity so that it is necessary to strengthen character through religion. This research uses qualitative research methods through analysis of literature, literature and related sources. So that information is produced regarding the analysis of the importance of the role of religious psychology in the formation of character and religious spirit in adolescents. Which is expected to be useful for academics and the wider community. Keywords: Psychology of Religion; Character Building; Teenagers.   Abstrak Perkembangan remaja sangatlah dipengaruhi oleh lingkungan yang ada disekitarnya. Terutama peran serta agama dalam pembentukan karakter dan kepribadian remaja. Peran psikologi agama dalam perkembangan remaja sangatlah kompleks karena berhubungan dengan fitrah dan keyakinan terhadap ajaran agama, nilai-nilai kebenaran dan juga menjadikan agama sebagai pedoman dalam sikap dan prilaku. Adanya perkembangan pandangan agama seseorang sejalan dengan perkembangan jasmani dan rohaninya. Karena usia remaja merupakan masa Dimana seseorang masih mencari jati dirinya sehingga perlu adanya penguatan karakter melalui agama. Dalam penelitian ini menggunakan metode penelitian kualitatif melalui analisis literatur, kepustakaan serta sumber terkait. Sehingga dihasilkan informasi mengenai analisis pentingnya peran psikologi agama dalam pembentukan karakter dan jiwa agama pada remaja. Yang diharapkan dapat bermanfaat untuk akademisi dan masyarakat luas. Kata Kunci : Psikologi Agama; Pembentukan Karakter; Remaja.